PENGARUH ETOS KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PT. ANANDA JATAKA BAYU SEJAHTERA (AJBS) DI KOTA GRESIK - Syafii, Mochamad; Ulinnuha, Mohammad (GEMA EKONOMI, 2018)
This study aims to examine and prove the influence of work ethos and organizational culture on the performance of PT. Ananda Jataka Bayu Sejahtera (AJBS) in Gresik City. The research is imortant espectially on employee performance, to know work ethic of employee speed, accuract, efficiency and quality of employee kega how employee adapt to the internal environtment and internal regulations of the company made into written rules that are not in the labor law, this study uses quantitative approach with multiple linear regression analysis, the number of samples taken is 60 respondent and data collection is done by questionnaire to obtain data. And the result of this research is the ethos ape significant positive effect on performance in PT. AJBS in Gresik city. DOI : 10.5281/zenodo.3477648